The contribution of the hidden curriculum to gender inequality in teaching and learning materials: Experiences from Tanzania - Losioki, Bertha Erasto; Mdee, Hemed Karani (Asian Journal of Education and Training, 2023)
This study aimed to examine the contribution of the hidden curriculum to gender inequality in teaching and learning materials. Despite the efforts to have an official curriculum through school textbooks and learning materials. The hidden curriculum continued to encourage gender inequality through teaching and learning materials. The study examined the content and portrayal of males and females in primary school social studies textbooks. The study used a qualitative research approach and the documentary review method was used to gather information from books, published articles, and policy documents. The findings show that there was an improvement in addressing gender inequality in textbooks and learning materials. The findings show that the visibility and representation of females in textbooks have increased. However, gender roles were portrayed in stereotypical ideas and images that encourage gender bias. The study concluded that teaching and learning materials encourage a hidden curriculum that facilitates the underrepresentation of females and males in textbooks. Therefore, the Government in collaboration with the relevant authorities should ensure that the development of teaching and learning materials considers gender-responsive content and gender balance in role allocation. There is a need to increase awareness among reviewers and book authors on gender sensitivity in the preparation of teaching and learning materials in order to ensure adherence to gender equality principles.